Spatial and temporal variability of ammonia and other inorganic aerosol species - Chen, X. (2013)
Nitrogen deposition to the sensitive ecosystems in Rocky Mountain National Park (RMNP) has been increasing. Ammonia has been shown to be a large fraction of this nitrogen deposition, and sources in northeastern Colorado were found to be a significant contributor. In this work we report on the results from a small network of Radiello passive samplers to investigate the temporal and spatial variability of ammonia gas concentrations in northeastern Colorado. A URG denuder/filter-pack sampler was collocated with a Radiello passive sampler to provide a check on the accuracy of passive ammonia measurements and to provide information about complementary aerosol and trace gas species. These measurements showed seasonal variations in the concentrations of both particulate- and gas-phase aerosol components. The highest concentrations of ammonia occurred during summer months. These were almost twice the lowest concentrations, which occurred during spring and fall months. Ammonia also exhibited higher than expected concentrations during winter. There was considerable spatial variability in average ammonia concentrations, with May–August averages ranging from 3 μg m−3 in rural grasslands to 4–11 μg m−3 at suburban-urban sites to almost 30 μg m−3 in an area of intensive livestock feeding and farming operations. The large ammonia gradients near sources are expected for this primary pollutant with high deposition rates. The overall concentrations in this region are significantly larger than those measured in RMNP, which were around 0.5 μg m−3, and represent a large reservoir of ammonia that can be transported to RMNP with easterly winds.